2019
DOI: 10.17241/smr.2019.00388
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sleep Disturbance and Cognitive Emotion Regulation Strategies on Depressive Symptoms in Breast Cancer Patients

Abstract: Background and ObjectiveaaDepression and insomnia are highly prevalent and important distressing symptoms in breast cancer patients. And also, strategies to assist with cognitive emotions are important to help them cope with the stress of the disease. This study aimed to investigate the effects of sleep disturbance and these coping strategies on depressive symptoms in breast cancer patients. MethodsaaWe retrospectively reviewed the medical records of 119 breast cancer patients. Psychiatric assessments were don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
9
0
2
Order By: Relevance
“…Para ello se consideraron los estudios publicados en los últimos 6 años, así como las investigaciones que incluyeron muestras de pacientes con diversos tipos de cáncer. Los resultados revelaron que la población femenina con cáncer de mama es la más estudiada, en la cual las estrategias de regulación emocional desadaptativas juegan un papel importante en la aparición de otros síntomas (ansiedad o depresión), repercutiendo a su vez en el nivel de la calidad de vida relacionada con la salud (Lee et al, 2019). Por otro lado, el dolor también genera un impacto negativo en la mejora de la calidad de vida relacionada con la salud (Abu et al, 2017).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Para ello se consideraron los estudios publicados en los últimos 6 años, así como las investigaciones que incluyeron muestras de pacientes con diversos tipos de cáncer. Los resultados revelaron que la población femenina con cáncer de mama es la más estudiada, en la cual las estrategias de regulación emocional desadaptativas juegan un papel importante en la aparición de otros síntomas (ansiedad o depresión), repercutiendo a su vez en el nivel de la calidad de vida relacionada con la salud (Lee et al, 2019). Por otro lado, el dolor también genera un impacto negativo en la mejora de la calidad de vida relacionada con la salud (Abu et al, 2017).…”
Section: Discussionunclassified
“…ISN 2707-2207/ISSN 2707-2215 (en línea), enero-febrero, 2023, Volumen 7, Número 1 p 5478 reevaluación (Peh et al, 2017) y la reconstrucción cognitiva (Babore et al, 2019;Bahrami et al, 2017), así mismo se identificó que las estrategias de regulación emocional les permiten a los pacientes afrontar el proceso de enfermedad y evitar desarrollar estrés, ansiedad, depresión, etc. (Babore et al, 2019;Lee et al, 2019).…”
Section: Discussionunclassified
“…Research in the field of psychosocial-oncology has demonstrated a link between cognitive-emotion regulation and mental health (Garnefski & Kraaij, 2006;Sloan et al, 2017), as well as FCR. Recent studies among BC patients have found a significant, direct (Lee et al, 2019), and indirect link (i.e., mediated through personality traits, illness perception, and psychological well-being) between the use of negative cognitive-emotion regulation and greater FCR (Hosseini et al, 2023a(Hosseini et al, , 2023b. However, other studies failed to find associations between negative cognitive-emotion regulation with a reduction in FCR levels from before to after radiation therapy (Guimond et al, 2019).…”
Section: Cognitive-emotion Regulation As a Moderating Factormentioning
confidence: 99%
“…emotion regulation) influence the trajectories of their emotional distress and adaptation (Conley et al, 2016). Multiple studies in cancer populations (Baziliansky & Cohen, 2021; Boyle et al, 2017; Guimond et al, 2019; Hoyt et al, 2017; Lee et al, 2019; Manne et al, 2019; Marroquín et al, 2016; Wang et al, 2014) show that the use of more approach‐oriented (e.g. cognitively reappraising negative thoughts, emotion‐based acceptance, emotional expression) and less avoidance‐oriented (e.g.…”
Section: Introductionmentioning
confidence: 99%